Analisa Dalam Pengambilan Keputusan Penentuan Lokasi Usaha Menggunakan Metode Preference Selection Index (PSI) - Aditia Yudistira (Jurnal Ilmiah Computer Science, 2022)
This study is to recommend business places using the Preference Selection Index (PSI) method with criteria including rental costs, parking lots, location area, highway distance and distance of public facilities, so that the results of the application of this PSI method will provide an overview and recommendations for business actors in determining the location of business premises. The ranking results from the application of the Preference Selection Index (PSI) method in determining business locations obtained rank 1 with a final value of 0.923 obtained by alternative Location A, rank 2 with a final value of 0.791 obtained by alternative Location E, rank 3 with a final value of 0.79 obtained by alternative Location B, rank 4 with a final value of 0.747 obtained by alternative Location C, and rank 5 with a final value of 0.681 obtained by alternative Location D.